WORKPLACE SURVEILLANCE: BIG BROTHER IS WATCHING YOU? - Corneliu BÎRSAN; Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
Only recently workplace surveillance has become a real concern of the international community. Very often we hear about employers who monitor and record the actions of their employees, in order to check for any breaches of company policies or procedures, to ensure that appropriate behaviour standards are being met and that company property, confidential information and intellectual property is not being damaged. Surveillance at workplace may include inter alia monitoring of telephone and internet use, opening of personal files stored on a professional computer, video surveillance. But what if this monitoring or recording breaches human rights? In order to give practical examples for these means, we shall proceed to a chronological analysis of the most relevant cases dealt by the European Court of Human Rights along the time, in which the Strasbourg judges decided that the measures taken by the employers exceed the limits given by Article 8 of the Convention. After providing the most relevant examples from the Court’s case-law in this field, we shall analyse the outcome of the recent Grand Chamber Barbulescu v. Romania judgment. The purpose of this study is to offer to the interested legal professionals and to the domestic authorities of the Member States the information in order to adequately protect the right of each individual to respect for his or her private life and correspondence under the European Convention on Human Rights.